Treecat wars - Weber, David, 1952-; Lindskold, Jane M. (Weber, David, 1952- Star Kingdom., 2014)
The pioneer planet Sphinx may soon see war as the now Landless Clan seeks new territory, bumping into a rival treecat clan's turf. Without Stephanie Harrington on the planet to help them, Jessica and Anders work to save the treecats from themselves, and from a group of less-than-trustworthy xenoanthropologists.